Factores predisponentes para desarrollar insuficiencia renal en los pacientes que asisten a la unidad de Hemodiálisis del Hospital Isidro Ayora de la ciudad de Loja, periodo mayo a octubre de 2013 - Jaramillo Zamora, Cristofer Geovanny (2014)
This study is based upon chronic kidney disease, illness that is in growth each year. I was performed a descriptive, analytical and transverse study directed to 72 persons attending at hemodialysis in General Hospital Isidro Ayora, from may to october 2013. The objective was to know general causes relatives to chronic kidney disease. The information was obtained through the clinic histories analysis from the 72 patients with a CKD diagnostic and with a data collection sheet. After analise and process the obtained dates, the results shows that the principal diseases that cause the CKD are: arterial hypertension, diabetes mellitus type 2, systemic lupus erythematosus and primary glomerulopathy, being the male gender the most numerous of this patology, and the age groups between 51 and 60 years, included the older than 70 years old, are most affected, therefore, they are the individuals with high risk to have a chronic kidney disease (CDK).